Ganjar Pranowo's Branding Politics Through Instagram Media in the 2024 Presidential Election Contestation - Purwanto, Sandy; Mujab, Saeful (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This research is motivated by the use of social media by political actors to build political branding which is one of the strategies to increase the electability of one of the presidential candidates in the 2024 presidential election contest, namely Ganjar Pranowo. The purpose of this research is to find out the political branding displayed by Ganjar Pranowo on Instagram social media as a political media in strengthening his electability in the Contestation of the 2024 Presidential Election of the Republic of Indonesia. The method used in this research is a qualitative research method with a descriptive approach. The data collection technique in this research uses observation and documentation. The results showed that political branding carried out on Instagram @ganjar_pranowo, consisting of 4 categories, namely policy, person, party, and presentation.